(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2018)
The purpose and objectives of the article is introduction to the results of the questionnaire survey: «The state and problems of business planning in Ukraine» and therefrom determination of key problems, ways and means for their solution, priority scientific and methodological developments, ways to improve the teaching of the «Business Planning» discipline, and the client’s perception of this consulting service. The questionnaire was conducted by sending out via social networks (Facebook) proposals to participate in the survey with a link to the Google Docs Form. Structurally developed questionnaire was consisted of 4 parts: 1) representation of respondents about the purposes, aim and practicability of business; 2) self-evaluation of knowledge, skills and competencies, identification of methodical and scheme of business planning and identification of the main difficulties they faced; 3) assessment of the current position and conditions of the development of consulting business in the sphere of business planning; 4) summary measure about assessment of the state of development of business planning; determination of the most acute problems and prospects for its development. Based on the results of the questionnaire, a number of specific proposals have been developed concerning directions for further work to improve the training of developers and improving the quality of preparation of business plans, allaboration of scientific and methodological approach for teaching the discipline «Business Planning» in Ukrainian universities. Following proposals received respondents’ support: the development of the National Standard for Business Planning, and the preparation of a new in-depth and updated version of the Methodological Recommendations for Preparation, Review, Selection and Implementation of Business Plans. A number of specific proposals have been developed on the basis of the results of the questionnaire; it aimed at improving the teaching and methodological support of «Business Planning» discipline at Ukrainian higher education institutions